If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7n + -26 = -21 + -12n Reorder the terms: -26 + -7n = -21 + -12n Solving -26 + -7n = -21 + -12n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12n' to each side of the equation. -26 + -7n + 12n = -21 + -12n + 12n Combine like terms: -7n + 12n = 5n -26 + 5n = -21 + -12n + 12n Combine like terms: -12n + 12n = 0 -26 + 5n = -21 + 0 -26 + 5n = -21 Add '26' to each side of the equation. -26 + 26 + 5n = -21 + 26 Combine like terms: -26 + 26 = 0 0 + 5n = -21 + 26 5n = -21 + 26 Combine like terms: -21 + 26 = 5 5n = 5 Divide each side by '5'. n = 1 Simplifying n = 1
| (7x-6)(x^2-5x+1)= | | ln(x+2)-3=5 | | 7(3x+2)-5(4x-3)+1=0 | | 180(n-2)=1080 | | (x-3)(2x^2+2x-4)=0 | | x^2+2x-1=18 | | 3t^9(t-t^2+4t^3)= | | 9a+3a+a=9-22 | | 3x-6*0=12 | | 175.00+2.00=3.00x | | (a-2)(3a+4)(a+2)= | | 3.00x=630. | | -4k(k^(7/5)-5k^(1/5)) | | (6x-5)(x^2-5x+1)= | | h=16t^2-20t+150 | | 445= | | sin^2x=-3sinx+4 | | 1085=620(1+0.15t) | | 10-9p= | | (6x-5)(x^2-8x+1)= | | 2235.75=2200(1+0.25r) | | 2n/5n | | 15x^2-14x-49= | | 16an-19an+8b+9an+12b= | | (X)(x-2)(x-6)=96 | | 8a+12a-7b-9b-11b= | | -3y+9=0 | | logx^2-logx+20=0 | | 7y-(10y-9x)= | | -5b-5=0 | | Lnx^2-Lnx+20=0 | | (x-7)+x+(2x-14)=67 |